2015
DOI: 10.1667/rr13708.1
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Effects of Mitochondria-Targeted Antioxidant SkQR1

Abstract: We show here that mitochondria-targeted antioxidant composed of plastoquinone conjugated through hydrocarbon linker with cationic rhodamine 19 (SkQR1) protected against nuclear DNA damage induced by gamma radiation in K562 erythroleukemia cells. We also demonstrate that SkQR1 prevented the early (1 h postirradiation) accumulation of phosphorylated histone H2AX (γ-H2AX) an indicator of DNA double-strand break formation, as well as the radiation-induced increase in chromosomal aberrations. These data suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…509 Another mitochondria-targeted quinone, SkQR1, was reported to be the substrate of multidrug resistance pump P-glycoprotein (Pgp 170) and to selectively protect Pgp 170-negative cells against oxidative stress. 510 Conversely, SkQR1 did not protect Pgp170-positive K562 subline against DNA damage induced by gamma radiation. The selective radioprotection of normal Pgp 170-negative cells by mitochondria-targeted antioxidants could be a promising strategy to increase the efficiency of radiotherapy for multidrug-resistant tumors.…”
Section: Mitochondria-targeted Therapeutics In the Pre-clinical Momentioning
confidence: 95%
“…509 Another mitochondria-targeted quinone, SkQR1, was reported to be the substrate of multidrug resistance pump P-glycoprotein (Pgp 170) and to selectively protect Pgp 170-negative cells against oxidative stress. 510 Conversely, SkQR1 did not protect Pgp170-positive K562 subline against DNA damage induced by gamma radiation. The selective radioprotection of normal Pgp 170-negative cells by mitochondria-targeted antioxidants could be a promising strategy to increase the efficiency of radiotherapy for multidrug-resistant tumors.…”
Section: Mitochondria-targeted Therapeutics In the Pre-clinical Momentioning
confidence: 95%
“…Several reports have shown that delayed production of ROS from mitochondria is observed in human hepatocellular carcinoma HLE cells [10,11], HeLa cells [12,13], human umbilical vein endothelial cells (HUVECs) [14], human leukemic cells K562 cells [15,16], HL60 cells [16], normal human foreskin fibroblast BJ-hTERT cells [17], and Chinese hamster ovary cells [18] after exposure to ionizing radiation. Moreover, it has been reported that the antitumor genotoxic drugs cisplatin- [19] and doxorubicin- [20] induced ROS release from mitochondria is linked to tumor apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…While the role of mitochondrial alterations in RIHD are not yet known, studies in other organ systems have shown a clear contribution of mitochondria to normal tissue radiation injury. Hence, mitochondrially-targeted antioxidants and antioxidant enzyme mimetics serve as radiation protectors and mitigators (11, 12). To determine whether POLY-MVA could slow down or reverse the adverse effects of radiation in the heart, the current study was designed to start POLY-MVA administration at 18 weeks after local heart irradiation, a time point at which manifestations of RIHD have become apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in organ systems other than the heart have shown a clear contribution of mitochondria to normal tissue radiation injury (11, 12). Radiation-induced heart injury in rodent models has been shown to be associated with mitochondrial dysfunction (13, 14).…”
Section: Introductionmentioning
confidence: 99%